The Empire writes back: views on Europe from Hispanic America in the middle of the nineteenth century - Grafl, Florian (Views on Europe, 2022)
Das Kapitel The Empire Writes Back. Views on Europe from Hispanic America in the Middle of the Nineteenth Century erschien in Views on Europe auf Seite 71.